Fifth Lumbar L5 Perineural Cyst with Unusual Radiculopathy: Traction Plexopathy - Rustagi, Tarush (Cureus, 2018)
Perineural cysts are cystic dilations and are frequently seen in relation to the lumbosacral spine. We describe a case of a fifth lumbar (L5) perineural cyst with unusual radicular symptoms and discuss the possible role of traction plexopathy caused by the cyst. A 38-year-old male presented with a longstanding history of back pain and right side thigh pain. This pain radiated from the buttocks to the lateral and anterior aspect of the thigh. He described the pain as pins and needles/burning with no significant relief with medications or rest. Imaging of the lumbar spine revealed a cystic lesion on the right side involving the L5 nerve root in the foraminal region. He failed conservative treatment and elected to have the cyst removed even with a guarded prognosis. A wide L5 laminectomy was performed. Due to the size of the cyst which was causing traction on the exiting L5 nerve root, the L5 pedicle was excised in order to delineate the cyst and to prevent any iatrogenic injury to the root. The patient had the dramatic improvement in his radicular pain immediately after the surgery and continues to be pain-free at his latest three-year follow-up. This case highlights the unusual pain pattern distribution from a perineural cyst possibly secondary to traction effect of the tumor.